Pan-European aquaculture data base project by FEAP. The Greek contribution - Theodorou J. (Marketing of aquaculture products, 1996)
In order to respond to the challenges of international competition, producers must manage their business in a professional way as regards to all aspects of their activities from production management to marketing. The continuous data flow for the final product availability is a strategic tool for marketing and price policy planning at both national and European level. The aim of the present paper is to demonstrate the development of a Pan-European databank project by FEAP in order to support the decision makers of the industry with facts and figures relevant with the volumes of the marketable fish and prices. The contribution by the Federation of Greek Maricultures is also discussed.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/10/11-13, Thessaloniki (Greece)